Temporal and spatial change of habitat quality and its driving forces: The case of Tacheng region, China - Ge, Yisong; Li, Chengzhi; Zhang, Tai; Wang, Bin (Frontiers in Environmental Science, 2023)
Habitat quality assessment is an important basis of ecological restoration. Taking the Taheng region as an example, the INVEST model was used to evaluate the habitat quality of the Tacheng region in five periods from 2000 to 2020, and analyzed the reasons for its changes, so as to provide theoretical guidance for ecological restoration planning in arid areas. The conclusions were that: From 2000 to 2020, the habitat quality in Tacheng region improved slightly, and the value of the habitat index in the Tacheng region was the highest in 2010, which was 0.577, and then decreased slightly; The regional habitat quality in the Tacheng region was greatly influenced by land use type conversion and precipitation. The conversion among forest land, grassland, and unused land was the main factor affecting the habitat quality change in the Tacheng region. Precipitation was also an important factor affecting the habitat quality change in the Tacheng region, which affected the biomass of natural vegetation and then affected the habitat quality; In the Tacheng region, the ecological restoration planning should select appropriate ecological restoration measures according to the causes of habitat quality changes.